Decrypting the Education-Job Match of Women Economic Migrants from Leyte and Samar - Sumagaysay, Marieta B. (Review of Women's Studies; Vol 26 No 1-2 (2016): Review of Women's Studies Volume XXVI, Numbers 1-2 (January-December 2016), 2023)
It is imperative to look into the education-job match of women economic migrants as this may indicate the degree of their social protection as reflected in their income-generating capacity abroad, and their consequent ability to financially assist the family left behind in times of uncertainties. Do the women economic migrants' foreign jobs match their educational preparation in the Philippines? How close are their pre-migration jobs to their current and/or first foreign jobs? Do their pre-migration jobs match their educational qualifications? In November and December 2011, twenty-one women economic migrants from Leyte and Samar were interviewed using the information technology superhighway, i.e., skype, chat, FB, viber, YM, Twitter, SMS. These are women who migrated as a result of a family decision aimed at protecting the family at home from future risks/failures. Results showed that while in the Philippines, women's jobs were generally related to their educational preparation. However, migration resulted with women getting jobs that were unrelated to their Philippine jobs. After some time, women economic migrants assimilated in the host country labor market, and searched for other jobs. These new/nth jobs are more related to their first foreign jobs, but the match goes as low as 43 percent only between the new/nth foreign jobs and the women economic migrants' educational preparation in the Philippines.